2009
DOI: 10.1007/s10661-009-1203-3
|View full text |Cite
|
Sign up to set email alerts
|

Dispersion and retrievability of water quality indicators during tidal cycles in coastal Salaya, Gulf of Kachchh (West coast of India)

Abstract: Bacterial indicators in relation to tidal variations were studied at five locations for over 2 days covering three tidal cycles in the southwestern region of Gulf of Kachchh, India. Tidal flow here is predominantly in the east west direction and can transport particles up to 32 km. Tidal amplitude appears to play a prominent role in abundance, distribution, and dispersal of coliform bacteria examined during this study. Shallow depths, clayey sediments, strong currents, and higher tidal amplitudes appear to ris… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 11 publications
2
3
0
Order By: Relevance
“…Similarly to the present investigation, Mohandass, Kumar, Ramahiah and Vethamony (), found that strong currents and flow appear to play a prominent role in dispersion of bacteria in coastal Salaya (India). The pollutant concentrations of the sources were chosen considering, that the sites where the shrimp ponds discharge their effluents have antibiotics concentrations of 3.0 mg L −1 (Le & Munekage ).…”
Section: Discussionsupporting
confidence: 87%
“…Similarly to the present investigation, Mohandass, Kumar, Ramahiah and Vethamony (), found that strong currents and flow appear to play a prominent role in dispersion of bacteria in coastal Salaya (India). The pollutant concentrations of the sources were chosen considering, that the sites where the shrimp ponds discharge their effluents have antibiotics concentrations of 3.0 mg L −1 (Le & Munekage ).…”
Section: Discussionsupporting
confidence: 87%
“…In the present study from Indian waters, the coliform and Streptococci were lowest during post monsoon and highest during monsoon. A similar pattern was also reported in Indian coastal zones such as Tamil Nadu beaches [1], Cauvery river estuary [14], Tamirabarani river estuary [13], Mandovi and Zuari estuary [4], Gujarat waters [29], the Visakhapatnam coast [3], and Mumbai waters [30]. …”
Section: Discussionsupporting
confidence: 78%
“…Transport of FIO in coastal waters is driven via tides and currents, allowing their movement from a source, such as rivers and streams, to a distant bathing water or away from it (Kim et al, 2004) and currents also influence bacterial population decay by cell separation (de Brauwere et al, 2014). Flooding tides tend to dilute nearshore FIO sources which results in a reduction in bacterial concentration (Boehm & Weisberg, 2005; Coelho et al, 1999; Mohandass et al, 2010). Falling ebb tides may allow drainage of IE generated in tidal saltwater marshes and beach aquifers (Boehm et al, 2004) causing an increase in concentrations of FIO in bathing waters (Boehm et al, 2004; Grant et al, 2001).…”
Section: Biological Chemical and Physical Factors Influencing Bathing...mentioning
confidence: 99%